Ultrasonographic evaluation demonstrating safer needle–organ distances in a novel quadratus lumborum block technique in cats - Takusagawa, Fumihiko; Takusagawa, Yoshimi; Kimura, Taro (Frontiers in Veterinary Science, 2026)
IntroductionWe investigated the relationship between needle placement and adjacent organs using ultrasonography during a novel quadratus lumborum block (QLB) performed in sternal recumbency and the conventional QLB performed in lateral recumbency among cats undergoing elective ovariohysterectomy.MethodsFourteen client-owned female cats were randomly allocated to the conventional QLB group (n = 7) or the novel QLB group (n = 7). For the conventional QLB group, the ultrasound probe was positioned at the second lumbar vertebra, whereas for the novel QLB group, it was placed at the intertransverse space between the second and third lumbar vertebrae. Probe angle was standardized at 90° using a 180° protractor, and tilted views were obtained at 70°, 80°, 100°, and 110°. The 90° image served as the needle insertion reference. OsiriX was used to identify organs within 5 mm of the needle shaft and to measure distances from the needle shaft, entry point, and needle tip to the nearest organs on the 90° image. Distances from a hypothetical entry point projected onto the tilted images were also evaluated.ResultsCompared with the conventional QLB group, the novel QLB group had fewer organs within 5 mm of the needle shaft on the right side. The novel QLB group also showed greater distances from the needle shaft and entry point to the nearest organs, as well as a shorter distance from the needle tip to the nearest organ. In tilted images, no between-group differences were identified except at 100° on the left side, where the novel QLB group had a longer distance. Blood vessels were the structures most frequently identified near the needle pathway.DiscussionThe novel QLB positioned the needle trajectory farther from vital organs, particularly on the right side, supporting its potential safety advantage. Real-time ultrasonographic visualization remains necessary because organs were still identified parallel to the trajectory or distal to the needle tip.